The sexual contract - Pateman, Carole (Standford University Press, 1988)
In this remarkably original work of political philosophy, one of today's foremost feminist theorist challenges the way contemporary society functions by questioning the standard interpretation of an idea that is deeply embedded in American and British political thought: that our rights and freedoms derive from the social contract explicated by Locke, Hobbes, and Rousseau and interpreted in the United States by the Founding Fathers.
Keywords: 1900-1999; 1980-1989; amériques; citoyenneté; contrat social; cours; discipline; droits des femmes*; fem1000; incontournable; philosophie politique; premier cycle; périodes historiques; régions géographiques; sciences humaines; thématiques; théories féministes; états-unis

Narcissism, femininity and alienation - Bartky, Sandra Lee (Social Theory and Practice, 1982)
Keywords: amériques; cours; discipline; fem1000; féminisme marxiste; philosophie politique; premier cycle; ressource en ligne; régions géographiques; sciences humaines; sexualité; thématiques; états-unis